Kinetic oscillation stimulation as treatment of non-allergic rhinitis: an RCT study. (May 2014) - Juto, Jan-Erik; Axelsson, Maria
Abstract: Conclusion: Kinetic oscillation stimulation (KOS) of nasal mucosa at low frequency seems to be a possibly effective and safe short-term treatment of non-allergic nasal stuffiness. Objective: To assess the relief of rhinitis symptoms, especially stuffiness, by comparing active treatment, i.e. KOS at low frequency of the nasal mucosa, with placebo. Methods: Patients were randomized to active or placebo treatment in this double-blinded parallel design study. Treatment with an inflatable oscillating catheter was administered on day 0, and symptom scores (stuffiness, secretion, and itching) were graded daily until day 14. An overall grading of symptoms from 1 week before treatment and during 14 days thereafter was made at day 14. Eighty-six patients (52 with non-allergic perennial rhinitis, NAR; 34 with rhinitis medicamentosa, RM) were randomized, and 71 were evaluated (active treatment, n = 35; placebo, n = 36). Results: Patients with either NAR or RM who received active treatment reported reduced symptom scores by some measures, e.g. median RQSS stuffiness measure fell from 2 to 1 on a scale from 0 to 3 during the week following treatment. No significant effect was observed for patients treated with placebo. Mild side effects were reported.